Entrepreneurs’ self-perception of skills in rural tourism in the North of Portugal - Castro, Conceição (Conferência - Investigação e Intervenção em Recursos Humanos, 2018)
Tourism is rural areas has gained importance as a way to compensate the decline of traditional rural activities, as agriculture, and rural exodus, enhancing the attractiveness of these areas, and micro and small enterprises play an important role in this process. Entrepreneur’s skills are an important part of the success but there aren’t studies of these skills in rural tourism in the North of Portugal. The region has attracted more and more tourists and includes two regions that are UNESCO Heritage sites. Based on Phelan and Sharpley (2012) entrepreneurial and personal maturity skills, the objective of this article is to study the perception of these skills among owners of rural tourism businesses in the North of Portugal. Based on a survey it was conducted a factor analysis to categorize the skills that load on two distinct factors which explained 73% of the variance. One of the factors includes skills of emotional coping, networking and accountability, while the other factor includes skills of business and strategic planning, environment scanning, persuasive communication and negotiation although the perceptions of these skills are lower than the included in factor one. According to the perception of the different skills, and through a cluster analysis, the entrepreneurs were aggregated in three different groups and was analyzed the profile of each group. The owners/managers of rural tourism businesses encountered some restrictions in the start-up process as the bureaucracy, the lack of financial support and of information. Understand the self-perception of entrepreneurs skills can help in defining strategies to enhance them in order to promote success and local development.